Marketing Challenges of Social Enterprise in UK Healthcare Sector: The Case of Nottingham CityCare Partnership - Park, Jeena (2012)
This project is written in parallel with the consulting project of Stakeholder Analysis of Nottingham CityCare Partnership which is supposed to serve to prioritize CityCare’s key stakeholders particularly in relation to developing a marketing strategy where key stakeholders and priorities identified as well as important opportunities and threats are highlighted. As a staff-led social enterprise and Community Interest Company, CityCare is faced by several challenges due to the complex nature of social enterprise with multi-stakeholders. The main aim of this research is to identify the main challenges of social enterprises in UK healthcare sector in terms of marketing in the deployment of their stakeholder engagement, and to provide answers to the following research questions. How can social enterprises in UK healthcare brand themselves? What factors should they consider for better marketing? In this paper, those challenges associated with the organisations internal management, such as mission, governance and innovation, are in turn examined. The context of marketing both of social enterprise and in healthcare industry are also applied in the analysis. Findings indicate that there are challenges facing CityCare in learning process, innovation and branding. Especially two main marketing challenges 1) Dilemma between brand visibility versus invisibility of CityCare and 2) low flexibility on marketing due to limited budget allowed. Based on the extensive literature review and case study of the environmental condition around CityCare, the paper suggests CityCare can maintain the balance between different values, develop various engagement processes and be opened to more partnerships as well as relationship marketing and social marketing for strategic approach.